Acute Biophysical Responses and Psychological Effects of Different Types of Forests in Patients With Metabolic Syndrome. Issue 3 (April 2018) - Lee, Kyung Ju; Hur, Junguk; Yang, Kyung-Sook; Lee, Mi-Kyoung; Lee, Sung-Jae
We aimed to examine the biophysical and psychological effects of two different types of forests on women with metabolic syndrome (MetS). Seventy-one middle-aged Korean women participated in a half-day healing program at either Saneum Recreational Forest (a wild forest) or Seoul Forest (a tended forest) depending on their preference. The participants' biophysical parameters and Profile of Mood States (POMS) were measured before and after the healing program. The two groups differed significantly in acute insulin responses, pulse rate, oxidative stress markers, and stress hormone level, suggesting better homeostasis in the wild forest. The POMS suggested that the mean vigor and confusion scores significantly decreased in the wild forest. Considering the significantly more favorable acute insulin reaction and levels of oxidative stress and the trend toward positive mood state in the wild forest, we recommend that middle-aged patients with MetS participate in healing programs in wild forests.